Thoth Archiving Network: Supporting Small and Scholar-led Publishers with Repository-Led Preservation of OA Books - Cole, Gareth; Barnes, Miranda; Steiner, Tobias (Septentrio Conference Series, 2023)
Watch VIDEO. Small and scholar-led presses make up much of the “long tail” of publishers without an active preservation policy in place, putting their significant contributions to the scholarly record at risk. As a recent study dissecting the archiving and preservation status of Open Access books suggests, there is “reason for concern for the long tail of OA books distributed at thousands of different web domains as these include volatile cloud storage or sometimes no longer contained the files at all” (Laakso, 2023). And while large-scale publishers have existing agreements with digital preservation archives, such as CLOCKSS and Portico, small presses often languish without financial or institutional support, alongside challenges in technical expertise and staff resources (cf. Barnes et al. 2022). There are similar concerns over the long tail of open access journal publishers and projects like Project JASPER are working on preservation options for OA journals with no current preservation in place. The Thoth Archiving Network, a recently-launched community initiative developed under the remit of the Community-led Open Publication Infrastructures for Monographs (COPIM) project, seeks to address this gap and help small and scholar-led book publishers with finding ways to preserve their publications for generations to come. The Thoth Archiving Network would not solve every issue, but it will be an initial step towards essential community infrastructure, allowing for presses to use a push-button deposit option to archive their publications in multiple repository locations. This will create an opportunity to safeguard against the complete loss of their catalogue should they cease to operate. With this presentation, we would like to provide an overview of the first steps taken so far to establish the Network, with a proof-of-concept now in place that provides a simple dissemination workflow for small publishers to archive their monographs in a network of participating institutional repositories (Internet Archive, Figshare/Loughborough, and, soon, DSpace/Cambridge). Several universities have already expressed their interest, and the team working on the Thoth Archiving Network would like to extend an invitation for more university repositories to take part, particularly from outside the UK. The Thoth Archiving Network receives funding from the Research England Development Fund and Arcadia under the Open Book Futures project grant, which has been awarded to significantly expand and accelerate uptake of the open infrastructures developed in COPIM.